On the Performances Investigation of Different Surface Mounted Permanent Magnet Machines - Mansouri Ali; Msaddek Hejra; Trabelsi Hafedh (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
In recent years, permanent magnet machines have become a common choice in many industrial applications. Therefore, several structures have been developed, and the choice of a topology designed for a specified application requires the knowledge of the advantages and disadvantages of different topologies. The present work deals with the evaluation of the performances of different radial flux surface-mounted permanent magnet motors designed for an electric vehicle motor application. The objective of this survey is to show the effect of the rotor position (inner or outer) and the magnets segmentation on the machine output torque and iron losses. In this context, four machines with: (i) inner rotor, (ii) inner rotor segmented magnets, (iii) outer rotor and (iv) outer rotor segmented magnets have been designed and studied. All these machines have the same geometrical dimensions and current loading. The main idea is to develop a machine with smoothness torque, lower torque ondulation, lower iron losses, and which is mechanically robust. Firstly, the output torque of the different structure is computed. Secondly, by means of an improved analytical model coupled with 2 dimensional transient finite element analysis (FEA), the machines iron losses are predicted.